Stratigraphy and sedimentology of the Niger Delta - Reijers, T.J.A. (Geologos, 2011)
During the Cenozoic, until the Middle Miocene, the Niger Delta grew through pulses of sedimentation over an ocean-ward-dipping continental basement into the Gulf of Guinea; thereafter progradation took place over a landward-dip-ping oceanic basement. A 12,000 m thick succession of overall regressive, ofﬂapping sediments resulted that is com-posed of three diachronous siliciclastic units: the deep-marine pro-delta Akata Group, the shallow-marine delta-front Agbada Group and the continental, delta-top Benin Group. Regionally, sediment dispersal was controlled by marine transgressive/regressive cycles related to eustatic sea-level changes with varying duration. Differential subsidence locally inﬂuenced sediment accumulation. Collectively, these controls resulted in eleven chronostratigraphically conﬁned delta-wide megasequences with considerable inter-nal lithological variation. The various sea-level cycles were in or out of phase with each other and with local subsidence, and interfered with each other and thus inﬂuenced the depositional processes. At the high inﬂection points of the long-term eustatic sea-level curve, ﬂoodings took place that resulted in delta-wide shale markers. At the low inﬂection points, erosional channels were formed that are often associated, downdip, with turbidites in low-stand sediments (LSTs). The mega-sequences contain regional transgressive claystone units (TST) followed by a range of heterogeneous ﬁne-to-coarse progradational or aggradational siliciclastic (para)sequence sets formed during sea-level high-stand (HST). An updated biostratigraphic scheme for the Niger Delta is presented. It also updates a sedimentation model that takes into consideration local and delta-wide effects of sea-level cyclicity and delta tectonics. Megasequences were for-med over time intervals of 5 Ma within individual accurate megastructures that laterally linked into depobelts. The megasequences form the time-stratigraphic frame of the delta and are the backbone for the new delta-wide lithostrati-graphy proposed here. Such a new lithostratigraphy is badly needed, in particular because of the vigorous new activity in the offshore part of the Niger Delta (not covered in this contribution). There, as well as in the onshore part of the delta, the traditional lithostratigraphic subdivision of the Cenozoic Niger Delta section into three formations is insufﬁcient for optimum stratigraphic application; moreover, the various informal subdivisions that have been proposed over time are inconsistent.